Faith: How to be Partial while Respecting the Evidence. Issue 1 (2nd January 2021) - Haderlie, Derek; Miller, Taylor-Grey
ABSTRACT: Some think that partiality is normative requirement of faith. Katherine Dormandy disagrees, arguing that partiality runs afoul of epistemic norms that faith requires. We offer an account of how one can respect the partiality requirement while respecting the epistemic norms as well. Central to the account is the role that confrontation plays in negotiating faith relationships where one has damning evidence about the object of faith. We claim that in confrontation one satisfies these seemingly competing norms for faith.